Mimicry honeypot: an evolutionary decoy system. (24th July 2019) - Shi, Leyi; Cui, Yuwen; Han, Xu; Chen, Honglong; Liu, Deli
Motivated by the mimic-and-evolve phenomenon for species rivalry, we present a novel concept of mimicry honeypot, which can bewilder the adversaries through comprehensively exploiting the protective coloration, warning coloration and mimicry evolution according to the changes of network circumstance. The paper firstly gives the definition of the protective coloration and warning coloration for cyber defence, formalises the mimicry honeypot model, discusses the environment perception and mimicry evolution issues, and implements a mimicry prototype through web service platform and genetic algorithm. Afterwards, we perform experiments with the mimicry prototype deployed both in our private campus network and on the internet. Our empirical study demonstrates that the mimicry honeypot has better efficiency than the traditional decoy system.